Profitability, Liquidity, and Tax Aggressiveness: Corporate Governance in Consumer Goods: Dampak Profitabilitas dan Likuiditas terhadap Agresivitas Pajak: Peran Tata Kelola Perusahaan pada Sektor Barang Konsumsi - Tyas Arifta Windasari; Santi Rahma Dewi (Academia Open, 2023)
This quantitative research investigates the relationship between profitability, liquidity, tax aggressiveness, and the moderating effect of corporate governance in consumer goods sector companies listed on the Indonesia Stock Exchange. A sample of 27 companies was selected using purposive sampling technique. The data was analyzed using the SmartPLS program, employing both outer and inner models. The study reveals that profitability significantly influences tax aggressiveness, while liquidity does not. Furthermore, the moderating variable of corporate governance does not have a significant effect on the relationship between profitability, liquidity, and tax aggressiveness. These findings contribute to the understanding of the factors influencing tax behavior in consumer goods sector companies and provide implications for policymakers, tax authorities, and corporate governance practitioners in designing effective strategies to manage tax aggressiveness. Highlights: Profitability significantly influences tax aggressiveness. Liquidity does not have a significant impact on tax aggressiveness. Corporate governance does not moderate the relationship between profitability, liquidity, and tax aggressiveness. Keywords: Profitability, Liquidity, Tax Aggressiveness, Corporate Governance, Consumer Goods